A case of insulinoma confused with dumping syndrome after total gastrectomy - Bilen, Arzu; Mercantepe, Filiz; Bilen, Habib; Capoglu, Ilyas (Journal of Surgery and Medicine, 2022)
We present the case of a 70-year-old female patient with persistent hypoglycemia after total gastrectomy due to gastrointestinal stromal tumors. She was thought to have late dumping syndrome but was diagnosed with insulinoma after further examination. Dumping syndrome is mainly seen after stomach or esophageal surgery. It is divided into early dumping and late dumping syndrome. Late dumping syndrome is initially manifested by an exaggerated insulin response and reactive hypoglycemia after glucagon-like peptide-1 release. Diagnosis is based on clinical findings. Treatment mainly consists of reducing carbohydrate intake and not ingesting solid and liquid foods together. In cases where diet alone is not sufficient, acarbose, an α-glucosidase inhibitor that slows the digestion of carbohydrates, may be beneficial for late dumping. Octreotide can be used in resistant cases. However, the diagnosis of insulinoma, which leads to a similar clinical presentation in resistant dumping cases, should be kept in mind. Our patient who showed clinical signs of dumping syndrome after gastrectomy, and treatment-resistant hypoglycemia was diagnosed with insulinoma on the basis of further investigations. The patient’s symptoms resolved after surgery for insulinoma.